2019
DOI: 10.3390/app9163431
|View full text |Cite
|
Sign up to set email alerts
|

Technical Performance of an Inflatable Solar Dryer for Drying Amaranth Leaves in Kenya

Abstract: The technical performance of an inflatable solar dryer (ISD) to dry amaranth leaves (Amaranthus spp.) was investigated. To handle the drying of lightweight materials, modification was made by adding an air deflector and trays inside the ISD. Computational performance of the ISD solar energy system was evaluated using MATLAB Simulink. The estimated air mass flow in the inlet of the ISD was 0.75 kg/s. Using computational fluid dynamics (CFD), the uniformity of air distribution in the ISD was evaluated. The solar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
9
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 23 publications
1
9
0
Order By: Relevance
“…This suggests a potential capacity increase for the SBD when elevated drying racks are incorporated for drying maize grains. The shorter drying time achieved with the elevated drying racks is due to the air movement over and under the bed of grains on the racks as corroborated by [25]. However, as reported by [12], for grains on the tarpaulin, the air moves over the surface of the grains and increases the grain temperature at the top layer compared to the bottom layer.…”
Section: Comparison Between Moisture Variation Using Elevated Racks and Drying On Tarpaulinsupporting
confidence: 65%
“…This suggests a potential capacity increase for the SBD when elevated drying racks are incorporated for drying maize grains. The shorter drying time achieved with the elevated drying racks is due to the air movement over and under the bed of grains on the racks as corroborated by [25]. However, as reported by [12], for grains on the tarpaulin, the air moves over the surface of the grains and increases the grain temperature at the top layer compared to the bottom layer.…”
Section: Comparison Between Moisture Variation Using Elevated Racks and Drying On Tarpaulinsupporting
confidence: 65%
“…The increase in temperature under GTSD was made possible due to the combined effect of greenhouse and suitable design of the base of the dryer and glazing materials. Romuli et al (2019) and Chauhan and Kumar (2016) also observed increased temperature of drying air. The present study corroborates with the findings of Alonge et al (2012) who reported that the maximum 0 temperature (51 C) was obtained in direct passive solar dryer as 0 compared to 38 C of ambient temperature.…”
Section: Resultsmentioning
confidence: 87%
“…The maximum overall drying efficiency was 39.9%.with PCM at the air flow rate of 0.025 kg/s. (Romuli et al, 2019). Tegenaw et al, (2017Tegenaw et al, ( , 2019b analyzed the marching heat transfer in a solar food (sweet potato) dryer by using both lumped capacitance modeling and computational fluid dynamics (CFD) techniques.…”
Section: Cfd Model Solution Proceduresmentioning
confidence: 99%
“…Figure 15. Visualization of airflow distribution and direction in the ISD (isometric and side view) and vertical flow through the 21 trays (top view)(Romuli et al, 2019).…”
mentioning
confidence: 99%